3. Раскройте скобки и приведите подобные слагаемые в выражении: -(4,3a+1,2b)+(1,7b-0,7a)-(2,1b-6,1a)

lol1045 lol1045    2   24.12.2020 13:46    0

Ответы
nurikparik nurikparik  23.01.2021 13:48

0,1a-1,6b

Пошаговое объяснение:

-(3,3а+1,2b)+(0,7b-1,7a)-(1,1b-5,1a)=

= -3,3а-1,2b+0,7b-1,7a-1,1b+5,1a=

= (-3,3а-1,7a+5,1a)+(-1,2b+0,7b-1,1b)=

= 0,1a-1,6b

ПОКАЗАТЬ ОТВЕТЫ
vladduliman5 vladduliman5  23.01.2021 13:48

-4,3а - 1,2b + 1,7b - 0,7a - 2,1b + 6,1a =

1,1a - 1,6b

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика